PERENCANAAN STRATEGIK PENCEGAHAN KECANDUAN GADGET PADA SISWA SMP (Studi Kasus di SMPN Satu Atap Pasirmunjul) - Permana, Tatang; Supriatna , Acep; Dahtiar, Dadan; Nurmuminah, Ina; Handayani, Sri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study explores the strategic planning model implemented at SMPN Satu Atap Pasirmunjul to prevent gadget addiction among junior high school students. Using a qualitative descriptive approach with case study methods, data were collected through interviews, observations, and document analysis. The research found that the Digital Sehat Program was designed collaboratively between school leaders, teachers, students, and parents. The program includes vision formulation, team structuring, SOP development, student digital ambassadors, educational activities, counseling services, and extracurricular engagement. The strategic planning process is responsive to the local context and prioritizes preventive, educational, and character-building approaches. Although the evaluation system remains basic, the program demonstrates potential for sustainability and replication. The school succeeded in fostering a digital culture that promotes balanced and responsible gadget use among students. Keywords: Strategic Planning, Gadget Addiction, Digital Literacy, Junior High School, Student Character